Nanophase‐separated poly(acrylic acid)/poly(ethylene oxide) plasma polymers for the spatially localized attachment of biomolecules. Issue 5 (18th December 2019) - Pleskunov, Pavel; Nikitin, Daniil; Tafiichuk, Renata; Khalakhan, Ivan; Kolská, Zdeňka; Choukourov, Andrei
Abstract: Carboxyl‐enriched nanoparticles are produced by the plasma polymerization of acrylic acid (ppAA NPs), whereas plasma‐assisted vapor‐phase deposition is used to prepare thin films of poly(ethylene oxide) (ppPEO). Sequential depositions generate phase‐separated coatings. The ppAA NPs are found to be in a glassy state, whereas thin films of ppPEO are found to be in a rubbery state. When immersed into a solution of lysozymes, the ppPEO absorbs water, which results in the dissociation of the carboxyls on the ppAA NP surface. Negatively charged carboxyls attract positively charged lysozymes. The ppPEO surface in between the NPs resists the accumulation of the protein, leading to the spatially localized adsorption of lysozymes only on the spots where the ppAA NPs are located. Abstract : Nanophase‐separated coatings are prepared by the sequential plasma‐assisted vapor‐phase deposition of poly(ethylene oxide) (PEO) and by the deposition of nanoparticles of plasma‐polymerized acrylic acid. When in solution, positively charged lysozyme molecules adsorb locally to negatively charged spots where the nanoparticles with dissociated COOH groups are embedded, whereas PEO resists the protein adsorption in‐between